Partial Purifi cation, Stability Analysis, and Preservation of Xylanase from Xylanolytic Alkalophylic Bacteria - Chusnul Hanim; Muhamad Nur Cahyanto; Lies Mira Yusiati; Ali Wibowo (Universitas Gadjah Mada, 2013)
A xylanase, which produces xylose from oat spelt xylans, was isolated from the culture medium of xylanolytic alkalophylic bacteria mutant. The enzyme was purifi ed by ammonium sulphate with level 30, 40, 50, 60, 70, 80, and 90%. The purify of the fi nal preparation was demonstrated by sodium dodecyl sulphatepolyacrylamide gel electrophoresis. The molecular masses of the purifi ed xylanase were 137.61 and 165.34 kDa. Result of ammonium sulphate saturation with the highest activity was used as standart for saturation for enzyme production and preservation, using corn, tapioca, soy bean meal and gaplek fl our as carriers. Addition of 60% ammonium sulphate showed the highest xylanase activity (62.03 U/g), and produced 89.40% enzyme recovery. Tapioca, as a carrier, produced the highest xylanase activity. Key words: preservation, purifi cation, stability analysis, xylanase.